Psychometric evaluation of Persian version of the balanced measure of psychological needs scale among university students - Hamid Sharif Nia; Pardis Rahmatpour; Fatemeh Khoshnavay Fomani; Gokmen Arslan; Omolhoda Kaveh; Saeed Pahlevan Sharif; Harpaljit Kaur (Wiley, 2021)
Abstract Aim The purpose of the present study was to evaluate the reliability, validity and factor structure of the Persian version of the BMPN in Iranian university students. Design Cross‐sectional. Methods Study was conducted among Iranian medical sciences students from April to May 2020. A total of 660 students participated in the online self‐administrated questionnaire. Construct validity, convergent and divergent validity, and reliability of P‐BMPN were evaluated. Results The Exploratory factor analysis showed that the Persian version of the BMPN has 17 items with four factors: dissatisfaction, autonomy Satisfaction, relatedness satisfaction and competence satisfaction that explained 40.17% of the total variance. Based on confirmatory factor analysis, all goodness‐of‐fit indices confirmed the model fit. Conclusion These results suggest that the Persian version of the BMPN is a reliable and valid measure to assess satisfaction and dissatisfaction of the psychological needs in Iranian university students.